(untitled) (The South East European Journal of Economics and Business, 2025)
This research explores the impact of cultural distance (CD) on Türkiye’s outward foreign direct investment (OFDI) by examining Hofstede’s six cultural dimensions, focusing on a country that shares several similarities with other Southeast European (SEE) countries. Using panel ordinary least squares, random effect, and quantile regression models, the study analyzes Türkiye’s OFDI to 26 partner countries from 2001 to 2022. The findings reveal a statistically significant positive effect of CD on OFDI, consistent across all cultural dimensions. This research enhances the limited literature on the relationship between CD and OFDI in Türkiye. The divergent findings provide new insights, highlighting the importance of understanding the nuanced dynamics between CD, cultural incongruence, and cultural conflicts in FDI. These results underscore the necessity for a contextual approach in examining the interplay between cultural factors and FDI, offering a more comprehensive understanding of how CD influences OFDIs.